2011
DOI: 10.1111/j.1468-036x.2011.00591.x
|View full text |Cite
|
Sign up to set email alerts
|

Political Connections, Financing Friction, and Corporate Investment: Evidence from Chinese Listed Family Firms

Abstract: Using a sample of Chinese family firms from 2000 to 2007, we investigate the investment behaviour of family firms and the effects of these firms' political connectedness on their investments in a relationship-based economy. Consistent with previous evidence that Chinese family firms have difficulty in financing, our results demonstrate that underinvestment due to problems with asymmetric information rather than overinvestment resulting from problems of free cash flow prevails in such firms. We further find tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
139
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(142 citation statements)
references
References 66 publications
3
139
0
Order By: Relevance
“…At the very least, the relatively higher prevalence of entrepreneur-and family-controlled firms in regions with high institutional efficiency suggests that these firms do not inhibit growth and development as is sometimes argued (Morck et al (2005). (Fan et al, 2007a;Chen et al, 2011;Xu et al, 2013Xu et al, , 2015 …”
Section: Discussionmentioning
confidence: 94%
“…At the very least, the relatively higher prevalence of entrepreneur-and family-controlled firms in regions with high institutional efficiency suggests that these firms do not inhibit growth and development as is sometimes argued (Morck et al (2005). (Fan et al, 2007a;Chen et al, 2011;Xu et al, 2013Xu et al, , 2015 …”
Section: Discussionmentioning
confidence: 94%
“…At the same time, family firms may be more likely to enter new industries related to their original businesses because of their aversion to risk (Patel & Chrisman, 2014). In addition, Chinese family firms suffered political and social discrimination because of China's socialist ideology (Su, Fung et al, 2013;Su, Zhang et al, 2013;Xu, Xu, & Yuan, 2013) and therefore find it more difficult to enter government-regulated industries than do non-family firms. However, some family firms expand their areas of investment by fostering connections with the government.…”
Section: Introductionmentioning
confidence: 96%
“…Specifically, we contrast family firms with non-family firms and reveal the significant differences between them in their choices of transformation mode. Second, the extant literature on the effects of political connections focus on firm performance (Muttakin, Monem, Khan, & Subramaniam, 2015;Wu, Wu, Zhou, & Wu, 2012;Xu et al, 2015), investment behaviour (Xu et al, 2013;Zhou, 2013), market capabilities (Jia, 2015), and control structure (Chen, Li, Su, & Sun, 2011). We examine a new and important dependent variable: business transformation.…”
Section: Introductionmentioning
confidence: 99%
“…This effect could be examined from the comparison between the regression output of state-owned firm sample and non-state-owned firm sample. As Table 4 and appeared to bear lower external financing costs (Ling et al, 2016;Chen et al, 2016;Xu et al, 2013;Su and Fung, 2013). Two possible explanations are that, first, for the majority of the firms state ownership did have significantly encouraged them to be more "responsible" and consider more regarding internal cash flow level during investment decisions, even at the presence of lower financing costs; second, the counterintuitive results could suggest that while state firms might indeed enjoy less financial constraints as previous research indicated, the level of financial constraint, as KZ concluded, has a non-monotonic relationship with firm investment-sensitivity cash flow that resulted in the counterintuitive results in Table 4 and 5.…”
Section: Resultsmentioning
confidence: 99%
“…The study followed the FHP regression form of investment expenditure on firm cash flow and Tobin's Q value, all of which were weighted by firm fixed asset value. The regression was added to a politics dummy variable that controlled for potential effect of state ownership on firm investment expenditure, referring to numerous studies that have found that firms with political connections or higher state ownerships could demonstrate lower financing costs and a tendency to have uncommon investment behaviors (Ling et al, 2016;Chen et al, 2016;Xu et al, 2013;Su and Fung, 2013). This dummy variable would equal to 1 if the firm is indicated by CSMAR as a privately owned firms and 0 otherwise.…”
Section: This Study Used the China Stock Market And Accounting Researmentioning
confidence: 99%